COMMODITY-RELATED RISK APPETITE OBSERVED ON THE EXAMPLE OF METAL COMPLEX COMPANIES - Krpić, Jelena (Ekonomija - teorija i praksa, 2023)
The focus of the paper is on the identification of the tendency towards commodity risk and the measures taken for protection on the example of companies of the metal complex. The ability to determine the amount of risk that the Company can manage is reflected on the achievement of adopted strategic goals. The research was based on data disclosed in the integrated annual reports of mining companies for the year 2021. The aim of the work was to determine whether the Company's management opts for tolerance, exposure, transfer, or avoidance of commodity risk. Commodity risk is viewed as commodity risk of procurement and commodity risk of sale. After that, the measures taken for protection were analyzed, that is, when operational hedging is applied and when financial hedging is applied. It can be concluded that company management opts for a combination of measures in order to maximize profit, preserve cash flow, and maximize the value of the company.